Comparative study of organosolv lignins from wheat straw - Xu, F.; Sun, J.; Sun, R.; Fowler, P.; Baird, M.S.
Dewaxed wheat straw was treated with acetic acid.H2O (65/35, v/v), acetic acid.H2O (80/20, v/v), acetic acid.H2O (90/10, v/v), formic acid.acetic acid.H2O (20/60/20, v/v/v), formic acid.acetic acid.H2O (30/60/10, v/v/v), methanol.H2O (60/40, v/v)and ethanol.H2O (60/40, v/v)using 0.1
Keywords: WHEAT STRAW; LIGNIN; ORGANIC ACIDS; PHENOLICS; FT-IR; 13C NMR